Identification of isomeric cyclo(leu-pro) produced by Pseudomonas sesami BC42 and its differential antifungal activities against Colletotrichum orbiculare - Kim, Jiwon; Kim, Jin-Cheol; Sang, Mee Kyung (Frontiers in Microbiology, 2023)
Pseudomonas spp. produce various antimicrobial substances, including cyclic peptides, which have been shown to suppress fungal pathogens. In a previous study, Pseudomonas sesami BC42 was selected to control anthracnose caused by Colletotrichum orbiculare in cucumber plants, and the bioactive extract of strain BC42 inhibited fungal growth and development. In this work, preparative thin-layer chromatography was conducted to identify the antifungal compounds in the extract of strain BC42, and the portion of the extract that exhibited antifungal activity was further analyzed by gas chromatography-mass spectrometry.Three different isomers of the cyclic dipeptide, cyclo(Leu-Pro), were identified: cyclo(L-Leu-L-Pro), cyclo(D-Leu-D-Pro), and cyclo(D-Leu-L-Pro). Among these, 100 μg/mL of cyclo(L-Leu-L-Pro) significantly and more effectively inhibited the germination of conidia and appressorium formation and reduced leaf lesion size caused by C. orbiculare, relative to the control; cyclo(D-Leu-D-Pro) significantly reduced conidia germination and lesion occurrence, however, cyclo(D-Leu-L-Pro) did not exhibit antifungal activity. Therefore, the cyclo(L-Leu-L-Pro) and cyclo(D-Leu-D-Pro) derived from P. sesami BC42 may be a promising candidate for biocontrol applications in agriculture.